The Effects of Stakeholder Collaboration on Academic Performance and Institutional Effectiveness: A Case Study of Three Secondary Schools in the OR Tambo Inland District in the Eastern Cape of South Africa - Vuyokazi Maqhubela (E-Journal of Humanities, Arts and Social Sciences)
Stakeholder collaboration plays a pivotal role in enhancing academic performance and institutional effectiveness in secondary schools. This paper examines the effects of collaboration among key stakeholders, including faculty, administration, students, external industry partners, and community members, on both student outcomes and the overall effectiveness of secondary schools. This paper is underpinned by the Collaborative Governance Theory which posits that multi-stakeholder collaboration can effectively improve institutional outcomes by leveraging diverse perspectives, resources, and expertise. The theory emphasizes the importance of shared decision-making and collective action, which are crucial in navigating complex organizational environments like schools. A sample of one rural university was selected for this study, with a focus on the experiences, behaviours, and social interactions of 3 parents, 3 learners, 3 teachers, and 1 school principal in each school. Based on the study’s interpretive paradigm, it was discovered that schools with well-integrated collaborative frameworks are better positioned to foster student success, maintain competitive relevance, and ensure long-term institutional growth. The study recommended that schools formalize collaborative processes by creating clear frameworks that define the roles and responsibilities of all stakeholders, including faculty. It was further recommended that schools should actively seek partnerships with industry, alumni, and community organizations. This study contributes to the growing body of literature on collaborative governance and its implications for achieving academic excellence and sustainable institutional development in the higher.